Social Factors Involved in Second Language Learning: A Case Study from the Pacific Campus, Universidad de Costa Rica - López Montero, Rosberly (2014)
This article presents the results obtained from an investigation carried out with students enrolled in the English Teaching Major from the Pacific Campus of the University of Costa Rica. The investigation is based on a case study supported by the qualitative paradigm. The main objective is to explore different social conditions that influence the effective learning of a second language. The analysis and interpretation of the data was done according to the strengths and limitations found. Through this study, factors such as motivation, cultural background and economic status have proven to be crucial in the language acquisition process of these students.